Measurements of the electric form factor of the neutron up to Q2=3.4 GeV2 using the reaction He3(e,e'n)pp; Physical Review Letters; Vol. 105, № 26 - Riordan S.; Abrahamyan S.; Craver B.; Kelleher A.; Kolarkar A.; Miller J.; Cates G. D.; Liyanage N.; Wojtsekhowski B.; Acha A.; Allada K.; Anderson B.; et al. (2010, 2010)
The electric form factor of the neutron was determined from studies of the reaction He3(e,e'n)pp in quasi-elastic kinematics in Hall A at Jefferson Lab. Longitudinally polarized electrons were scattered off a polarized target in which the nuclear polarization was oriented perpendicular to the momentum transfer. The scattered electrons were detected in a magnetic spectrometer in coincidence with neutrons that were registered in a large-solid-angle detector. More than doubling the Q2-range over which it is known, we find GEn = 0.0225 +/- 0.0017 (stat) +/- 0.0024 (syst), 0.0200 +/- 0.0023 +/- 0.0018, and 0.0142 +/- 0.0019 +/- 0.0013 for Q2 = 1.72, 2.48, and 3.41 GeV2, respectively